Kondisi perekonomian indonesia pasca covid 19 - Nurazizah Nurazizah; Rizkika Khairatun Hisan; Najwa Atanya; Abdan Masykuri; Irnawati Irnawati (Journal on Education, 2024)
The Covid-19 pandemic has had a significant impact on the Indonesian economy, causing a decline in economic growth, increasing poverty levels and pressure on the business sector. This article presents an analysis of the condition of the Indonesian economy after Covid-19, economic recovery, the role of Micro, Small and Medium Enterprises (MSMEs), global news, and international cooperation through the G20 forum. Even though there are signs of improvement in Indonesia's economic prospects, challenges remain, especially regarding the recovery of MSMEs which have been badly affected. It is hoped that continued support from the government, structural reforms and international cooperation will help Indonesia achieve a sustainable and inclusive economic recovery in the future.